Stand-alone hybrid microgrid for remote areas: topology and operation strategy - Battaiotto, Pedro Eduardo (2017)
In remote regions, were a main Utility System for energy distribution is not available, the implementation of Microgrids with hybrid generation are very useful. In this context, a Stand-Alone wind/diesel/gas/battery/supercapacitors Hybrid Microgrid topology is proposed. The main scope is to create a low cost system to feed Residential loads through a local AC bus, using wind energy obtainable at system location. The random characteristics of the wind makes necessary to smooth the fluctuating supply in order to minimize the disturbances on local grid electric parameters. To overcome these problems, a Wind Turbine based on a DFIG machine and Strategies to control the power of a Storage Energy System are employed. An appropriate Supervisor Module with a reliable communication network is used to balance generation and loads, in order to properly operate the Microgrid. The system structure, operation modes and mathematical models for simulation and validation are presented.